Anticoagulant effects of combined extracts of Curcuma xanthorrhiza Roxb., Mimusops elengi Linn., and Averrhoa carambola in mice - Rahminiwati, Min; Ulandari, Rafika; Hidayat, Rahmat (Current Biomedicine, 2025)
Background Curcuma xanthorrhiza Roxb. rhizome, the Mimusops elengi Linn. leaves, and Averrhoa carambola leaves contain bioactive compounds such as alkaloids and flavonoids. Flavonoids influence calcium ion levels, which play critical roles in cardiovascular functions, including heart function and blood coagulation. However, the effects of these plant extracts on blood clotting remain unclear. Objective This study aimed to evaluate the anticoagulant effects of a combination of these plant extracts in mice. Methods Twenty-five mice were divided into five treatment groups, receiving either distilled water (0.5 mL/25 g BW), aspirin (0.2 mg/20 g BW), Curcuma xanthorrhiza extract (0.1344 mg/20 g BW), or a combination of the three extracts at two doses (0.63 mg/20 g BW and 2.52 mg/20 g BW). Extracts were administered orally, bleeding and coagulation times were measured at 3-, 6-, and 9-hours post-administration. Results The combined extract significantly prolonged bleeding and coagulation times compared to a single Curcuma xanthorrhiza extract. The most pronounced effect was observed at a dose of 2.52 mg/20 g BW, with the peak effect occurring at the 3rd hour. Conclusion The combination of Curcuma xanthorrhiza, Mimusops elengi, and Averrhoa carambola extracts demonstrated significant anticoagulant activity, with the highest potency observed at a dose of 2.52 mg/20 g BW, surpassing the effects of aspirin. The synergistic interaction between these extracts is suggested to enhance their anticoagulant properties.